A pitfall in ultrasonographic diagnosis-heterotopic corneal pregnancy initially misdiagnosed as leiomyoma - C. Chan; J. W. Wang; C. W. Wang; C. W. Chang (Clinical and Experimental Obstetrics & Gynecology)
Background: Ultrasound has become a routine examination of early pregnancy especially pregnancy after in vitro fertilization and embryo transfer (IVF-ET). However, benign pelvic pathology such as uterine myoma, hydrosalpinx, and endometrioma may mislead the clinicians’ interpretation. Case Report: A patient of heterotopic cornual pregnancy following IVF-ET, which had been misdiagnosed as uterine leiomyoma in serial ultrasound scans, and ruptured at 12 gestational weeks. Conclusion: This case report reminds us the versatility of an ectopic pregnancy. Clinicians need to record in detail the position and size of any uterine mass before commencing infertility treatment. Any newly developed mass could be misdiagnosed, even in the presence of an intrauterine pregnancy. The possibility of heterotopic pregnancy (HP) must be kept in mind if more than one embryo was transferred.